A new snapping species of the shrimp genus Typton Costa, 1844 (Decapoda: Palaemonidae) from the coast of São Paulo, southeastern Brazil - Almeida, Alexandre O.; Anker, Arthur; Mantelatto, Fernando L. (Zootaxa, 2014)
A new species of the palaemonid shrimp genus Typton Costa, 1844, Typton fapespae sp. nov., is described based on several specimens collected in Ubatuba and São Sebastião, northern coast of the state of São Paulo, Brazil. Most specimens were found in association with sponges, including Mycale (Zygomycale) angulosa (Duchassaing & Michelotti, 1864) (Demospongiae: Mycalidae); however, one paratype from Ubatuba was extracted from a colony of the bryozoan Schizoporella errata (Waters, 1878) (Gymnolaemata: Schizoporellidae). In T. fapespae sp. nov., the posterodorsal margin of the sixth abdominal segment bears a strong median tooth, a feature shared with T. hephaestus Holthuis, 1951, T. holthusi De Grave, 2010 and T. spongicola Costa, 1844. However, the new species can be separated from each of these three species by at least two morphological features.